The myth of the rational voter why democracies choose bad policies - Caplan, Bryan Douglas 1971- (Princeton University Press, 2007)
"Caplan argues that voters continually elect politicians who either share their biases or else pretend to, resulting in bad policies winning again and again by popular demand. Calling into question our most basic assumptions about American politics, Caplan contends that democracy fails precisely because it does what voters want. Through an analysis of American's voting behavior and opinions on a range of economic issues, he makes the case that noneconomists suffer from four prevailing biases: they underestimate the wisdom of the market mechanism, distrust foreigners, undervalue the benefits of conserving labor, and pessimistically believe the economy is going from bad to worse. Caplan lays out several ways to make democratic government work better